Significance of Basic Fibroblast Growth Factor (BFGF) in The Development of Postresuscitation Changes in Population of Cerebellar Purkinje Cells - M. Sh. Avrushchenko; I. V. Ostrova (Общая реаниматология)
Objective: to evaluate the relationship of postresuscitation changes in the level of bFGF protein expression and morphological patterns of the cerebellar Purkinje cells.Materials and methods. Albino adult male rats were subjected to 10 minutes of systemic circulatory arrest caused by cardiac vascular fascicle ligation. The status of a hypoxiasensitive neuronal population of cerebellar Purkinje cells were investigated in different postresuscitation periods. Total numbers of Purkinje cells per mm of their layer length were estimated by a histological analysis of the specimens stained with cresyl violet after the Nissl procedure. An immunocytochemical analysis was performed to determine the number of bFGFpositive (weakly and strongly stained) and GDNFnegative neurons per mm of their layer length and the total population density.Results. Dynamics of the process of neuronal death and changes of bFGF expression level in the population of the Purkinje cells were determined postresuscitation. Next day after the resuscitation the level of expression of bFGF in the neuronal population significantly increased. At the same time point, the neuronal death did not occur. However, on day 4 the level of bFGF expression decreased and overall density of the population declined. Immunohistochemical study revealed that bFGFnegative cells undergone death. In the later stages of the process postresuscitation (days 7 and 14) the bFGF expression level increased again. At the same time deepening and/or enhancing of the pathological changes in the neuronal population were not observed.Conclusion. The data indicate that ischemiareperfusion significantly affect the expression of bFGF protein, inducing its elevation within the Purkinje cell population of resuscitated animals. The initial rise in the level of bFGF protein within the neuronal population might prevent the development of a nerve cell death process. The subsequent reduction in the bFGF level is accompanied by the neuronal loss. Therefore, the ability to produce bFGF is an important factor affecting the resistance of neurons to postresuscitation damage. Moreover, the bFGF is considered as promising candidate molecule for developing alternative therapeutic strategies to prevent and/or treatment posthypoxic encephalopathies.